DESCRIPTION, COMPOSITION, AND PROPERTIES OF COSTUME-GRADE WOOL FIBRE MATERIALS - Mahsudov Shohrukhmirzo Abdulhamid ogli; Abdurakhimova Manzura Sodiqovna (European Science Publishing, 2024)
This article provides an in-depth exploration of the description, composition, and properties of wool fibre materials utilized in the production of high-quality suit fabrics. It examines the structural characteristics and functional attributes of wool and its blends, highlighting the key requirements these materials must meet to ensure optimal performance and aesthetic appeal. Through a comprehensive analysis, the study delves into the definitions and classifications of wool and mixed fibre materials, outlining their respective advantages and disadvantages. The findings underscore the critical role of fibre composition in determining durability, comfort, and versatility, offering valuable insights into the development of innovative textiles for the apparel industry. Additionally, the article presents the impact of combining wool with synthetic and natural fibres on the final product’s mechanical, thermal, and tactile properties. The analysis aims to guide manufacturers and researchers in optimizing fibre combinations to achieve superior performance and sustainability in suit production.
Keywords: Wool fibre, composition, properties, requirements, wrinkle resistance, deformation resistance, abrasion resistance, pilling resistance, shape retention, aesthetic appearance, stable colour.